2016
DOI: 10.2113/econgeo.111.1.225
|View full text |Cite
|
Sign up to set email alerts
|

A Combined Ingress-Egress Model for the Kianna Unconformity-Related Uranium Deposit, Shea Creek Project, Athabasca Basin, Canada

Abstract: The Kianna deposit is an unconformity-related uranium deposit in the western Athabasca Basin of northern Saskatchewan, hosting uraninite in three distinct zones: 1) perched above the unconformity, hosted in sandstone; 2) at the unconformity, hosted in sandstone and basement rocks; and 3) below the unconformity in two separate pods, hosted by basement paragneiss. In situ secondary ion mass spectrometry (SIMS) was used to obtain radiogenic and stable isotope data to update the genetic model for the Kianna deposi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 56 publications
5
27
0
Order By: Relevance
“…1500 Ma is the age of the emplacement of the Kuungmi lavas over the Thelon Basin (1540±30 Ma, Chamberlain et al, 2010). This age was obtained in several studies throughout the Western-Churchill province (Turner et al, 2003;Bridge et al, 2013;Gandhi et al, 2013;Dieng et al, 2013;Sheahan et al, 2015) and is possibly linked to a regional thermal event possibly reflecting a craton-scale process. If this thermal event has reset the U-Pb isotopic system (Davis et al, 2011;Peterson et al, 2015b), then the ages of the first stage of faulting and mineralization could be bracketed between ca.…”
Section: First Stage Of Uranium Mineralizationmentioning
confidence: 72%
“…1500 Ma is the age of the emplacement of the Kuungmi lavas over the Thelon Basin (1540±30 Ma, Chamberlain et al, 2010). This age was obtained in several studies throughout the Western-Churchill province (Turner et al, 2003;Bridge et al, 2013;Gandhi et al, 2013;Dieng et al, 2013;Sheahan et al, 2015) and is possibly linked to a regional thermal event possibly reflecting a craton-scale process. If this thermal event has reset the U-Pb isotopic system (Davis et al, 2011;Peterson et al, 2015b), then the ages of the first stage of faulting and mineralization could be bracketed between ca.…”
Section: First Stage Of Uranium Mineralizationmentioning
confidence: 72%
“…Besides, detailed mineralogical and isotopic data showed that several episodes of U ore formation occurred around 1500 Ma, 959 Ma, 300 Ma (Fayek and Kyser, 1997;Kotzer and Kyser, 1995;Kyser et al, 2000). In the Kianna deposit, one of the U deposits in the Shea Creek area, Sheahan et al (2016) proposed a genetic model with formation of basement mineralization at about 1500 Ma, remobilization of this mineralization at around 1280 Ma and 1100 Ma, and uraninite mineralization in the sandstone at~750 and~500 Ma.…”
Section: Geological Backgroundmentioning
confidence: 99%
“…1). In this area, the thickness of the Athabasca Group sandstone is 700 to 800 m. The Shea Creek area was selected for the present study because it is a good example of the Athabasca unconformity-related uranium deposits with pods hosted in the basement and the sandstone (Sheahan et al, 2016). In addition, this choice was motivated by access to samples by AREVA and the excellent knowledge of this deposit area from numerous studies (e.g.…”
Section: Geological Backgroundmentioning
confidence: 99%
See 2 more Smart Citations